Crystallization, preliminary X‐ray crystallographic and cryo‐electron microscopy analysis of a bifunctional enzyme fucokinase/L‐fucose‐1‐P‐guanylyltransferase from Bacteroides fragilis. Issue 9 (1st September 2014) - Cheng, Chongyun; Gu, Jianhua; Su, Jing; Ding, Wei; Yin, Jie; Liang, Wenguang; Yu, Xiaoxia; Ma, Jun; Wang, Peng George; Xiao, Zhicheng; Liu, Zhi‐Jie
Abstract : Fucokinase/L‐fucose‐1‐P‐guanylyltransferase (FKP) is a bifunctional enzyme which converts L‐fucose to Fuc‐1‐P and thence to GDP‐L‐fucose through a salvage pathway. The molecular weights of full‐length FKP (F‐FKP) and C‐terminally truncated FKP (C‐FKP, residues 300–949) are 105.7 and 71.7 kDa, respectively. In this study, both recombinant F‐FKP and C‐FKP were expressed and purified. Size‐exclusion chromatography experiments and analytical ultracentrifugation results showed that both F‐FKP and C‐FKP are trimers. Native F‐FKP protein was crystallized by the vapour‐diffusion method and the crystals belonged to space group P 21 21 21 and diffracted synchrotron X‐rays to 3.7 Å resolution. The crystal unit‐cell parameters are a = 91.36, b = 172.03, c = 358.86 Å, α = β = γ = 90.00°. The three‐dimensional features of the F‐FKP molecule were observed by cryo‐EM (cryo‐electron microscopy). The preliminary cryo‐EM experiments showed the F‐FKP molecules as two parallel disc‐shaped objects stacking together. Combining all results together, it is assumed that there are six FKP molecules in one asymmetric unit, which corresponds to a calculated Matthews coefficient of 2.19 Å 3  Da −1 with 43.83% solvent content. These preliminary crystallographic and cryo‐EM microscopy analyses provide basic structural information on FKP.